2017
DOI: 10.1103/physrevb.95.195418
|View full text |Cite
|
Sign up to set email alerts
|

Collective scattering in hybrid nanostructures with many atomic oscillators coupled to an electromagnetic resonance

Abstract: There is considerable interest in collective effects in hybrid systems formed by molecular or atomic ensembles strongly coupled by an electromagnetic resonance. For analyzing such collective effects, we develop an efficient and general theoretical formalism based on the natural modes of the resonator. The main strength of our approach is its generality and the high level of analyticity enabled by modal analysis, which allows one to model complex hybrid systems without any restriction on the resonator shapes or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…As a consequence, a direct computation of all sub/super‐radiant states of the hybrid system becomes feasible in a small timescale by solving a generalized eigenproblem and some essential properties of hybrids, which are robust to spatial and polarization disorders, become predictable. For instance, it can be shown that the mean decay rate normalΓsup of the superradiant states, where denotes an ensemble average, scales linearly with the mean Purcell Factor Fp, evidencing that ultra‐bright hybrid states in large ensembles of emitters coupled via an electromagnetic resonance arise from the combination of Dicke and Purcell effects, and not from direct dipole‐dipole interactions like in the classical Dicke effect …”
Section: Strong Coupling and Superradiancementioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, a direct computation of all sub/super‐radiant states of the hybrid system becomes feasible in a small timescale by solving a generalized eigenproblem and some essential properties of hybrids, which are robust to spatial and polarization disorders, become predictable. For instance, it can be shown that the mean decay rate normalΓsup of the superradiant states, where denotes an ensemble average, scales linearly with the mean Purcell Factor Fp, evidencing that ultra‐bright hybrid states in large ensembles of emitters coupled via an electromagnetic resonance arise from the combination of Dicke and Purcell effects, and not from direct dipole‐dipole interactions like in the classical Dicke effect …”
Section: Strong Coupling and Superradiancementioning
confidence: 99%
“…The present period is marked by a deployment of QNM concepts in various applications, quantum plasmonics, spectral filtering with diffraction gratings, energy loss spectroscopy in plasmonic nanostructures, second‐harmonic generation in metal nanoparticles, coupled cavity‐waveguide systems, single‐photon antennas, ultrafast‐dynamics nanooptics, scattering‐matrix reconstruction in complex systems, spontaneous emission at exceptional points, wave transport in disordered media, spatial coherence in complex media, mode hybridization and exceptional points in complex photonic structures, random lasing, light localization and cooperative phenomena in cold atomic clouds, spatially nonlocal response in plasmonic nanoresonators, and thermal emission . We discuss some of these numerous applications of QNM concepts in this Review and Figure summarizes a few.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecule-nanoparticle electromagnetic interactions are central to many current research topics, beyond the illustrative examples treated in this work. Of particular interest will be the study of dielectric nano-resonators 33 with high quality factors, the dependence of strong coupling 29,34 on surface coverage and molecular orientation when the core particle sustains a resonance tuned with the molecular resonance, but also the influence of a core particle on superradiance 35 , or Föster resonant energy transfer 36,37 between collections of dipole emitters. The subtle changes in the polarisation properties of the local electric field have also promising applications in the understanding of surface selection rules and surface-enhanced optical activity near nanostructures.…”
Section: Discussionmentioning
confidence: 99%
“…S1). The theoretical framework is however much more general, and could readily be applied to other types of emitters or nanoparticles 32 , to dielectric nano-resonators 33 , and also in the context of strong coupling 29,34 , superradiance 35 , Föster resonant energy transfer 36,37 , and related effects involving near-field electromagnetic coupling between emitters in the vicinity of a nanoparticle 38 .…”
mentioning
confidence: 99%